2020
DOI: 10.3390/nu12123729
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Status and Low Awareness of Folate in Switzerland—A Call to Strengthen Public Health Measures to Ensure Sufficient Intakes

Abstract: Background: Folate plays an essential role in the prevention of neural tube defects, yet little is known about the folate status of women of reproductive age or to what degree the general population is aware of the importance of folate in early-life development. We aimed to determine folate status in women of reproductive age and pregnant women in Switzerland, and to assess folate awareness in the Swiss population. Methods: In a convenience sample of 171 women of reproductive age and 177 pregnant women through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(32 reference statements)
0
5
1
Order By: Relevance
“…The prevalence of folate deficiency and insufficiency found in our study population (9.6% and 86.5%, respectively) was much higher than that in neighbouring countries, since available data indicate that they were around 0-5% and 40-50%, respectively (18)(19)(20)(21)(22).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The prevalence of folate deficiency and insufficiency found in our study population (9.6% and 86.5%, respectively) was much higher than that in neighbouring countries, since available data indicate that they were around 0-5% and 40-50%, respectively (18)(19)(20)(21)(22).…”
Section: Discussioncontrasting
confidence: 63%
“…Despite growing awareness of the need for correct prenatal folate status, the limited data available indicate that folate deficiency and insufficiency are 0-5% (18)(19)(20)(21)(22) and 40-50% (19,22), respectively, in developed countries. As for clinical significance and based on WHO recommendations, folate deficiency refers to depleted folate stores while folate insufficiency indicates a high risk of NTD despite having folate reserves (19,(22)(23)(24). Furthermore, compliance of periconceptional FA supplementation remains low (25,26) while many women start it during the first months of pregnancy, when damage may already have occurred as a result of an inadequate folate level, if any (27).…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that the G-allele is favorable for folate accumulation in sweetcorn. In many populations, dietary folate intake is considerably lower than recommended level [2][3][4][5][6][7][8] . Because high levels of folates were detected in the heterozygous G/A corn, breeders may consider using the G-allele to breed high-folate corn varieties by means of the marker-assisted approach.…”
Section: Discussionmentioning
confidence: 99%
“…The human body cannot synthesize folates de novo and must capture folates from dietary foods 1 . Unfortunately, the dietary intake of folates is inadequate in both developing and developed countries [2][3][4][5][6][7][8] . The worldwide prevalence of neural tube defects, a severe disorder caused by folate deficiency, remains between 0.3 and 124.1 per 10,000 births 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Other observational studies found no direct association between low folate levels and pregnancy complications (16)(17)(18). To date, the role of folate intake to prevent NTD is veri ed (19,20). Most relevant studies adopted self-statement of multivitamin supplementation, which may be imprecise, so serum folate concentration during pregnancy would be more ideal.…”
Section: Introductionmentioning
confidence: 99%